A randomized controlled trial of the effectiveness of a onestep conditioning agent in sealant placement: 6-month results - L. BURBRIDGE, Z. NUGENT, & C. DEERY (Paediatric Dentistry, 2006)
The objectives of this study were: to compare the retention of fissure sealants (sealants) placed on occlusal surfaces following the use of a self-etching priming agent and traditional acid etch; to compare the caries incidence of occlusal surfaces sealed using the two techniques; and to compare the ease of placement of sealant following the use of the two techniques, as assessed by subjects and operators.